Majas dan Imaji Dalam Lirik Lagu Kimi Ga Kureta Natsu Karya Reo Ieiri - Nur Hastuti; Alya Nurul Inayah (KIRYOKU, 2022)
Poetry is a very famous literary work. Nowadays, song lyrics are considered a part of poetry as well. Song lyrics and similar poetry elements; such as rhymes, stanzas, etc. To make the lyrics more poetic, the lyricist can use some figures of speech and images in the lyrics. This study aims to determine the figure of speech and imagery in the song "Kimi ga Kureta Natsu" by Leo Ieiri. The method used in this research is the library method using stylistic studies as an analytical tool. The data used in this study are the lyrics of "Kimi ga Kureta Natsu" by Reo Ieiri. Based on data analysis, it can be concluded that in the lyrics of the song Kimi ga Kureta Natsu there are 3 types of figure of speech and there are 2 types of images.